2017
DOI: 10.1017/s0212610917000131
|View full text |Cite
|
Sign up to set email alerts
|

Evolución De Salarios Reales en Ecuador Durante La Gran Depresión, 1927-1937

Abstract: The monetary policies of the decade studied had a direct influence on the evolution of real wages in Ecuador. The gold standard brought with it the increase in real wages until 1932. In February 1932, the Ecuadorian Government decided to abolish the gold standard which, together with a heavy public expenditure, produced a significant increase in money supply causing high levels of inflation. The evolution of real wages in Ecuador is similar to the evolution registered in Latin America in two important aspects:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Within this context, the article develops three themes: economically active population and purchasing power; legal context on working conditions; and, a brief review on the implementation of the minimum wage in Ecuador and some Latin American countries. (Naranjo, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, the article develops three themes: economically active population and purchasing power; legal context on working conditions; and, a brief review on the implementation of the minimum wage in Ecuador and some Latin American countries. (Naranjo, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Presidential decrees from 1928 mentioned pensions from 66 to 143 sucres monthly for a primary teacher, equivalent to the average received in the last five years. In the third group, constructed from the economically active population found in the public sector, workers in industries and merchants, the data from Naranjo (2017) showed that the lowest-paid employees and workers had, on average, an income of 91 sucres per month within 1920s. However, these wages had fallen sharply during the international crisis: the Great Depression reduced unskilled wages by about 25 sucres from 1929 to 1935.…”
Section: Economically Active Population and Purchasing Powermentioning
confidence: 99%
“…Por otra parte, el interés por ofrecer nuevas evidencias sobre los salarios, precios y canastas de consumo popular se imbrica con las tendencias de la historiografía económica internacional que han puesto en la agenda el poder de compra de los salarios de los trabajadores como indicador de bienestar material ( welfare ratio ) (Bértola, Camou y Porcile (1999); Williamson (1999, 2002); Allen (2001); Bértola (2005); Arroyo Abad (2013); Challú y Gómez Galvarriato (2015); Astorga (2017); Moraes y Thul (2017); Naranjo Navas (2017); Zamberlan Pereira (2019). Sólo en parte este tipo de enfoques han sido aplicados al caso argentino y mendocino, a pesar de valiosos antecedentes que pusieron el foco en las características del mercado laboral, o más bien de mercados “limitadamente conectados entre sí” (Míguez, 2018, p. 177) y las condiciones de vida de los trabajadores.…”
Section: Introductionunclassified